2013
DOI: 10.4028/www.scientific.net/amr.748.61
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Screw Rotation Speed on Mechanical Properties of Extruded PLA/Kenaf Nanocomposites

Abstract: Extrusion is one of established methods of polymer processing with fibre and consequently disperses fibre inside polymer. Different speed shows different behaviour of fibre dispersion. This study was conducted to produce composites from polylactic acid and kenaf by extrusion method. Kenaf bast and core was undergone chemical treatment with sodium hydroxide (6% w/w) followed by hydrochloric acid. Then, kenaf bast and core was mechanically beaten to reduce the fibre size. PLA and kenaf fibre (bast and core) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…As it was discovered, PLA/kenaf bast and PLA/kenaf core exhibit improved results on flexural strength of 60 rpm rotation speed, and impact strength higher value was measured with PLA/kenaf bast and PLA/kenaf core at 70 rpm rotation speed. Jaafar et al [55] investigated the varying speeds of extrusion (60, 70, and 80 rpm) and showed various behavior of fiber dispersion. The effect of screw speeds of 40, 80, and 140 rpm extrude on the mechanical characteristics of PLA/HNT composite has been examined by Venkatesh et al [56].…”
mentioning
confidence: 99%
“…As it was discovered, PLA/kenaf bast and PLA/kenaf core exhibit improved results on flexural strength of 60 rpm rotation speed, and impact strength higher value was measured with PLA/kenaf bast and PLA/kenaf core at 70 rpm rotation speed. Jaafar et al [55] investigated the varying speeds of extrusion (60, 70, and 80 rpm) and showed various behavior of fiber dispersion. The effect of screw speeds of 40, 80, and 140 rpm extrude on the mechanical characteristics of PLA/HNT composite has been examined by Venkatesh et al [56].…”
mentioning
confidence: 99%